Methods Of Professional Training Of Students In The Vocational Education System - Khakimov Sodikjon Rasuljon o’gli (Journal of Innovation in Education and Social Research, 2023)
The specific content of the article examines the specific tasks of the methodology for professional training of students in the vocational education system.